Philosophy of Science and Philosophy of Islamic Science on Definition and Object of Study - Firdaus Ardianto; Zulhandra Zulhandra; Muklis M; Saipullah SA; Ahmad Husein (Studi Multidisipliner: Jurnal Kajian Keislaman, 2026)
This research aims to analyze the concept of philosophy of science and philosophy of Islamic science by focusing on the definition and object of study. This study is motivated by the importance of a philosophical understanding of science, both in the general perspective and in the Islamic scientific tradition, as the basis for the development of integrative and holistic science. The research uses a qualitative approach with the type of library research. Data was obtained from various sources of literature, such as books, scientific journals, articles, and academic documents relevant to the research theme. The data analysis technique is carried out through content analysis to identify, classify, and interpret the main concepts related to the philosophy of science and the philosophy of Islamic science. The results of the study show that philosophy of science is a branch of philosophy that discusses the nature of science, methods of obtaining knowledge, and the validity and purpose of science. Meanwhile, the philosophy of Islamic science not only focuses on rational and empirical aspects, but also places revelation as the main source of knowledge. The object of study of philosophy of science includes ontology, epistemology, and axiology of science, while philosophy of Islamic science expands the study through the integration of spiritual values, ethics, and Islamic principles in the development of science. This research emphasizes that the philosophy of science and the philosophy of Islamic science are closely related in building a comprehensive scientific paradigm oriented towards human benefit.